CCEA GCSE history - Madden, Finbar; Clare, John D. (Dynamic learning, 2017)
Exam board: CCEALevel: GCSESubject: HistoryFirst teaching: September 2017First exam: Summer 2019 Trust the experts to guide you through the new specification with this bestselling Student Book for CCEA GCSE History, fully updated to cover every option in a single volume; an authoritative and affordable solution to curriculum change from the leading History publisher. - Skilfully steers you through the new content and assessment requirements with support at every stage from experienced teachers and authors Finbar Madden and John Clare - Blends in-depth coverage of topics with activities to help students acquire, retain and revise core subject knowledge across the years - Builds students' historical thinking and writing skills as they progress through clear narrative and topic-focused tasks, brought to life by visual and written source material - Prepares students of all abilities for the non-tiered examinations by providing a variety of practice questions throughout each chapter - Enables students to maximise their grade potential and develop their exam skills through structured guidance on answering every question type successfully